1987
DOI: 10.1002/ajmg.1320260129
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant cerebro‐costo‐mandibular syndrome: Ultrasonographic and clinical findings

Abstract: We describe two patients, a father and his daughter, with the cerebro-costo-mandibular syndrome. New manifestations not previously described include microstomia, long philtrum, posterior cervical skin fold, short internipple distance, and depressed sacral region. The presence of hydrocephaly in the proposita and spina bifida in the father may be other manifestations of neuraxial involvement in this syndrome. The first intrauterine ultrasonographic documentation of this syndrome showed polyhydramnios and, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 10 publications
1
20
0
1
Order By: Relevance
“…Both an autosomal recessive [7][8][9][10] and autosomal dominant 6,11,12 pattern of inheritance has been described. No case has been described with a chromosome anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…Both an autosomal recessive [7][8][9][10] and autosomal dominant 6,11,12 pattern of inheritance has been described. No case has been described with a chromosome anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…Clarke and Nguyen described an infant, the product of a father/daughter union, who had microcephaly, a large porencephalic cyst and no definable ventricular system or interhemispheric fissure [2]. Merlob et al reported a patient with CCM whose in-utero ultrasound showed "a fluid-filled supratentorial" compartment [3]. Our patient is the third example of cerebral structural anomaly in CCM in the literature.…”
Section: Discussionmentioning
confidence: 76%
“…Microcephaly of postnatal onset may be present (40%), sometimes associated with structural cerebral anomalies [Plotz et al, 1996]. So far these have been detected in only three living patients by ultrasound and CT scan, and they include large porencephalic cyst and no definable ventricular system or interhemispheric fissure in one case; agenesis of the corpus callosum with ''enhancement'' of the right leaf of the tentorium and enlargement of both lateral ventricles in another, and ''fluid filled supratentorial'' compartment in yet another [Clarke and Nguyen, 1985;Merlob et al, 1987;Burton and Oestreich 1988]. Exceptionally, intrauterine growth retardation and rib anomalies could be seen by ultrasound examination during pregnancy, but usually prenatal diagnosis is very difficult and probably restricted to families with a positive history for CCMS [Merlob et al, 1987].…”
Section: Discussionmentioning
confidence: 97%